The Importance of Vaccines in Preventing Impending Alzheimer’s Epidemic - Tripathi, Siddhant; Sharma, Yashika; Kumar, Dileep (Reviews on Recent Clinical Trials, 2025)
The use of antibodies to neutralize cytotoxic soluble amyloid-β aggregates rather than remove plaque has raised cautious hope since the monoclonal antibody BAN2401 seems to halt the course of prodromal Alzheimer's Disease (AD). By immobilizing cytotoxic amyloid-β, rather than the causative factor, plaques can help prevent Alzheimer's disease. A preventive immunity against Alzheimer's disease is shown by natural antibodies against cytotoxic amyloid-β. Vaccines should include adjuvants that promote anti-inflammatory Th2 immunity and immunogens that guard against different cytotoxic amyloid-β conformers to prevent or delay the onsetof Alzheimer's disease. The lack of long-term protection with monoclonal antibodies that neutralize single conformers, such as aducanumab, may be due to amyloid-β pleomorphism. In this scenario, novel cytotoxic conformers might evade neutralization by monoclonal antibodies that were previously successful. A vaccine's ability to elicit a polarized Th2 immunity would depend on both priming and the simultaneous delivery of immunogen to dendritic cells. In addition to neutralizing antibodies against neurotoxic amyloid-β oligomers, an immune response may also release anti-inflammatory cytokines, which can help prevent inflammation that exacerbates Alzheimer's disease. Vaccines would be significantly more successful in preventing Alzheimer's disease than treating it because of age-related immunological decrease. Since both amyloid-β and tau contribute to pathological hyperphosphorylation and work in tandem to cause Alzheimer's disease, preventive vaccinations against both should be taken into consideration. Given their affordability and simplicity, vaccines may be the only way to stop the looming Alzheimer's pandemic in many nations.
Keywords: monoclonal antibody